Activity and characterization of antifungal compounds from the peel of sweet orange Citrus sinenesis fruits - Oluwole Olakunle Oladele; Abiola Titilayo Aborisade (Journal of Crop Protection, 2018)
Environmental risks associated with the use of synthetic fungicides have resulted in an emergent trend in plant disease control with focus on the use of botanicals. In this work, the peels of ripe sweet orange fruits were removed, air dried, powdered and extracted with 95% ethanol. The agar diffusion method was used to test the crude extract against the mould, Lasiodiplodia sp. IMI 50324 Which was originally isolated from rotten orange fruits. The extract inhibited mycelial growth of the fungus. The ethanolic extract was subsequently purified by column chromatography and the fractions separately tested for antifungal action. Total phenol contents of fractions and crude extract were both determined. Active fractions were pooled together and analyzed by gas chromatography-mass spectrometry (GC-MS) for structural elucidation. GC-MS revealed that the peel extract contained the flavonoid 5, 6, 7, 8, 3', 4'-hexamethoxyflavone which is commonly called nobiletin. The presence of 5, 6, 7, 8, 3', 4' hexamethoxyflavone in the peel together with the high total phenol content probably account for inhibition of the test fungus.